„Az észnek kurta szárnya” A Commedia ráción túli jelentésrétegeiről - Pál, József (Kultúratudományi Szemle, 2022)
After a brief comparison of Dante's hermeneutics and hermetism, the article chooses the following approaches to describe and define the theme: the theology of the limits of human intellectual abilities (rejecting the theses of the “velamists”); the analysis of the structural role of numbers as formal elements of a moral philosophy, posing the question whether we could suppose the validity of a heterodox cryptography? The various Dantesque attitudes are demonstrated in the three parts of the article.